Conservation as Foundation, Destination as the Future: Transforming Mangrove Ecotourism in Tapak Semarang through Community Empowerment and Innovation - Awanis Linati Haziroh; Dian Prawitasari; Febrianur Ibnu Fitroh Sukono Putra; Adilla Kustya Ulfa; Qonita Maharani; Nadira Rohadatul Aisy; Nico Alexander Vizano (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to transform a mangrove conservation area into an attractive and sustainable ecotourism destination through a community empowerment approach. The main partner of this program is the Tourism Awareness Group (POKDARWIS) of Tapak Village, Semarang City, which serves as a key actor in the management, development, and promotion of community-based mangrove ecotourism. The implementation methods consisted of field observations, focus group discussions (FGDs), training and counseling sessions, mentoring and hands-on practice, as well as evaluation and reflection. The assistance focused on developing structured ecotourism packages, strengthening digital marketing strategies, and improving service quality through the development of Standard Operating Procedures (SOPs). Data were analyzed using descriptive and comparative approaches to assess changes before and after program implementation. The results indicate increased community knowledge and skills in managing and promoting mangrove ecotourism, the establishment of structured tourism packages, the creation of digital promotional content, and the initial implementation of tourism service SOPs. The program significantly enhanced the readiness of local managers to receive visitors and created opportunities to improve the economic prospects of the local community. Therefore, this initiative contributes to the development of a community-based mangrove ecotourism model that emphasizes environmental conservation and local economic empowerment.